2015
DOI: 10.1007/s12094-015-1335-6
|View full text |Cite
|
Sign up to set email alerts
|

Early evaluation of targeted therapy effectiveness in non-small cell lung cancer by dynamic contrast-enhanced CT

Abstract: DCE-CT can evaluate targeted therapy efficacy at 7 days post-treatment. Decreased primary tumor diameter and BP indicate tumor sensitivity to therapy; increased BP with unchanged tumor diameter suggests the tumor is not sensitive to therapy. Reduced BP suggests treatment effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Scans were executed with tube voltage ranging from 80 to 120 kVp and tube current of 50–115 mAs. In four studies, patients received between 40 and 50 mL non-ionic contrast media, while Qiao et al dosed contrast media according to weight [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scans were executed with tube voltage ranging from 80 to 120 kVp and tube current of 50–115 mAs. In four studies, patients received between 40 and 50 mL non-ionic contrast media, while Qiao et al dosed contrast media according to weight [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…They also found significantly lower blood flow in responders than in non-responders 3–6 weeks after treatment. Qiao et al also found a significant decrease in blood flow in responders treated with anti-EGFR [ 30 ]. The same study showed that patients with a decrease in blood flow had a significantly longer median progression-free survival.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, CTP based on a single-input model has been investigated for the evaluation of various treatments of lung cancer, including chemotherapy, targeted therapy, radiotherapy and interventional therapy. The majority of these studies confirmed CTP as a useful method and found that BF and permeability surface (PS) product decreased after treatment (33)(34)(35)(36)(37). Few studies have been carried out on thermal ablation, and the results have varied.…”
Section: Discussionmentioning
confidence: 98%
“…CT perfusion was lower in RECIST responders versus non-responders at week 3 and week 6 respectively. Another study showed dynamic CT perfusion can used to early evaluate targeted therapy efficacy 7 days post-treatment and reduced blood perfusion suggests tumor sensitivity to therapy and treatment effectiveness [45].…”
Section: Prognostic Biomarker and Response Predictionmentioning
confidence: 99%